Climate governance at the crossroads experimenting with a global response after Kyoto - Hoffmann, Matthew J. (New York ; Oxford : Oxford University Press, 2011)
This volume explains how and why these new governance experiments have emerged, drawing upon a database of such initiatives to ascertain how these initiatives fit together and how they influence what is defined as environmental governance.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Environmental policy -- Government policy; Environmental policy -- International cooperation; Climatic changes -- Government policy; Climatic changes -- International cooperation